2009
DOI: 10.1111/j.1469-0691.2009.02824.x
|View full text |Cite
|
Sign up to set email alerts
|

Different virulence levels of the species of Sporothrix in a murine model

Abstract: A comparative study on the experimental pathogenicity of five species of Sporothrix of clinical interest, Sporothrix albicans, Sporothrix brasiliensis, Sporothrix globosa, Sporothrix mexicana, and Sporothrix schenckii sensu stricto, was performed using an immunocompetent murine model. Two strains of each species and two levels of inoculum for each strain (2x10(7) and 2x10(4) conidia/animal) were tested by intravenous inoculation of mice (ten per group). Mortality was caused by the low inoculum of one strain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
188
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(212 citation statements)
references
References 18 publications
9
188
1
7
Order By: Relevance
“…35 Some comparative studies were conducted correlating the route of experimental infection 32 or clinical manifestation in humans with the virulence degree of different isolates. 33,34 Recently, Arrillaga-Moncrieff et al 2,3 showed different degrees of virulence among S. schenckii s. str., S. brasiliensis and S. globosa species.…”
Section: Characterization Of Virulence Profile Protein Secretion Andmentioning
confidence: 99%
See 2 more Smart Citations
“…35 Some comparative studies were conducted correlating the route of experimental infection 32 or clinical manifestation in humans with the virulence degree of different isolates. 33,34 Recently, Arrillaga-Moncrieff et al 2,3 showed different degrees of virulence among S. schenckii s. str., S. brasiliensis and S. globosa species.…”
Section: Characterization Of Virulence Profile Protein Secretion Andmentioning
confidence: 99%
“…2,3 This is the first study which evaluates the protein secretion of S. brasiliensis, S. globosa and S. schenckii s. str. and connects the humoral immune response to virulence of these species.…”
Section: 124142mentioning
confidence: 99%
See 1 more Smart Citation
“…str.) showed marked heterogeneity in the virulence profiles studied 2,3 . Sporotrichosis has a worldwide distribution and is the most common subcutaneous fungal infection in South America 4 .…”
mentioning
confidence: 99%
“…Subsequently, studies have been conducted in order to elucidate the different levels of virulence and pathogenicity demonstrated by each species 2 . According to previous studies, S. brasiliensis demonstrated the highest pathogenicity and virulence, while isolates of S. schenckii sensu stricto (s.…”
mentioning
confidence: 99%